Exploring agro-ecological significance, knowledge gaps, and research priorities in arbuscular mycorrhizal fungi - Mwampashi, Lenganji Lackson; Magubika, Aneth Japhet; Ringo, Job Frank; Theonest, Dickson J.; Tryphone, George Muhamba; Chilagane, Luseko Amos; Nassary, Eliakira Kisetu (Frontiers in Microbiology, 2024)
This systematic review examines the global agricultural relevance and practical environmental implications of arbuscular mycorrhizal fungi (AMF) within the phylum Glomeromycota. Following PRISMA guidelines, ensuring a comprehensive and unbiased literature review, a literature search was conducted, focusing on the functional roles of AMF in enhancing crop productivity, nutrient uptake, and soil health. Key findings reveal that AMF contribute significantly to sustainable agriculture by reducing the need for chemical fertilizers and increasing plant resilience to environmental stressors like drought, salinity, or pest resistance. The review highlights the importance of AMF in forming symbiotic relationships with plants, which enhance nutrient absorption and improve soil structure, showcasing long-term benefits such as reduced erosion or improved water retention. However, the current literature lacks in-depth exploration of the taxonomy and evolutionary aspects of AMF, as well as the specific functional roles they play in different agricultural contexts, e.g., understanding evolution could enhance strain selection for specific crops. This review identifies several urgent research gaps, including a need for a more refined understanding of AMF community dynamics under varying land management practices. For example, there are gaps in and a critical evaluation of advanced molecular techniques. Such techniques are essential for studying these interactions. Addressing these gaps will enhance the integration of AMF into sustainable agricultural systems and improve ecosystem management practices across different geographical regions. Future research should prioritize developing precise molecular imaging techniques and optimizing AMF applications for different crops and soil types to maximize their ecological and agricultural benefits. This could be practical through interdisciplinary collaboration (e.g., involving molecular biologists, agronomists, etc.). In conclusion, this review advances the practical application of AMF in agriculture and its contribution to biodiversity conservation in agroecosystems. Integrating these findings into policy frameworks could encourage sustainable farming practices, promote the adoption of AMF inoculants, and foster incentives for environmentally friendly land management strategies.